Scurvy in a boy with knee pain and a limping gait: a case report - Draman, Samsul; Che' Man, Mohamad; Megat Ahmed Tahwil, Puteri Fatin Nabilah; Che Alhadi, Shahidah; Amiruddin, Salman (Journal of Critical Reviews, 2021)
Scurvy is a disease caused by chronic vitamin C deficiency which has become uncommon in the modern age. Several cases have been reported in children with restricted dietary habits with neurodevelopmental issues. It is often overlooked as an initial diagnosis in view of its vague presentations mimicking other systemic diseases which lead to extensive investigations and delay in diagnosis. A previously healthy 9-year-old boy with left knee pain and a limping gait presented to a local health clinic. The child subsequently developed worsening bilateral knee pain and was unable to walk without support. His restricted diet and radiographic findings were suggestive of scurvy which was confirmed by the extremely low levels of ascorbic acid. Treatment with ascorbic acid replenishment and maintenance resulted in remarkable improvement of his symptoms. This case highlights the importance of a high index of suspicion in at-risk children so as to avoid unnecessary invasive investigations and procedures